Identifikasi Sumber Bahaya Potensial, Penentuan Tingkat Risiko Dan Penetapan Sarana Pengendalian Berdasarkan Metode Hazard Identification And Risk Assessment Control (Hirac) Di Departemen Mekanik Pt. Indo Acidatama Tbk. Kemiri, ebakkramat, Karanganyar - Hasri, Yola novita; , Dr.Suwaji, M. Kes (2016)
PT. Indo Acidatama Tbk. Kemiri, Kebakkramat, Karanganyar is a company which moves in chemical industry on an International scale with ethanol, acetic acid, acetaldehyde, and ethyl acetate as the main product. The HIRAC method used for identified dangerous potential source, determine risk level, and decision control measures because the activity in this company would involve the entire element that there is a human factor, equipment/machine and working environment that cannot be clear from dangerous potential source. The kind of this research is analytics descriptive with the male labors as many as 27 people from PT. Indo Acidatama Tbk. Kemiri, Kebakkramat, Karanganyar mechanics department using exhaustive sampling technique. The result of research is 56 identified dangerous potential source with 40 (71,4%) dangerous potential source including medium risk level, 13 (23,2%) dangerous potential source including low risk level, and 3 (5,4%) dangerous potential source including high risk level. The dangerous potential source came from various kinds of work activity which come from the equipment and machine, how to work, work attitude, work environment, and completeness in using personal protective equipment.